2007
DOI: 10.1051/0004-6361:20077887
|View full text |Cite
|
Sign up to set email alerts
|

The abundance of SiS in circumstellar envelopes around AGB stars

Abstract: Aims. Given their photospheric origin and refractive nature, SiS molecules can provide major constraints on the relative roles of dust condensation and non-equilibrium processes in regulating the chemistry in circumstellar envelopes around evolved stars. Methods. New SiS multi-transition (sub-)millimetre line observations of a sample of AGB stars with varying photospheric C/O-ratios and mass-loss rates are presented. A combination of low-and high-energy lines are important in constraining the circumstellar dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
83
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 41 publications
(82 reference statements)
21
83
2
1
Order By: Relevance
“…When taking the abundance uncertainty into account, this agrees with the results of Schöier et al (2007), who find a value of 2 × 10 −6 from lowexcitation SiS lines. From observations of the 13.5 μm fundamental band of SiS, Boyle et al (1994) obtained a gradient in the abundance of SiS, going from 4.3 × 10 −6 at a distance of 12 R and rising to 4.3×10 −5 close to the stellar surface.…”
Section: Sissupporting
confidence: 81%
“…When taking the abundance uncertainty into account, this agrees with the results of Schöier et al (2007), who find a value of 2 × 10 −6 from lowexcitation SiS lines. From observations of the 13.5 μm fundamental band of SiS, Boyle et al (1994) obtained a gradient in the abundance of SiS, going from 4.3 × 10 −6 at a distance of 12 R and rising to 4.3×10 −5 close to the stellar surface.…”
Section: Sissupporting
confidence: 81%
“…More generally, Cherchneff (2006) studied the inner wind composition as a function of the carbon-to-oxygen (C/O) ratio of the stellar photosphere and confirmed the formation of O-bearing species in carbon stars and that of C-bearing molecules in O-rich AGB stars as a result of non-equilibrium chemistry induced by periodic shocks. Several observations of high energy rotational transitions of HCN, SiS, CS, and SiO in AGBs and supergiants at mm and submm wavelengths corroborated these results (e.g., Schöier et al 2006Schöier et al , 2007Ziurys et al 2007Ziurys et al , 2009Decin et al 2008).…”
Section: Introductionsupporting
confidence: 67%
“…As concerns previous observational studies, there is a general consensus on the presence of a gradient in the abundance of SiS, with reported values in the range 10 −6 −10 −5 in the inner layers (>6.5 × 10 −7 by Turner 1987; 7.5 × 10 −6 by Bieging & Nguyen-Q-Rieu 1989; 4.3 × 10 −5 close to the stellar surface decreasing down to 4.3 × 10 −6 at 12 R * by Boyle et al 1994) and reported values in the range 10 −7 −10 −6 in the outer envelope (2.4 × 10 −7 by Sahai et al 1984; 5 × 10 −7 by Nguyen-Q-Rieu et al 1984; 5 × 10 −7 by Henkel et al 1983; 1.5−4 × 10 −7 by Henkel et al 1985;6.5 × 10 −7 by Bieging & Nguyen-Q-Rieu 1989; 1.4 × 10 −6 by Schöier et al 2007). The more recent study of Decin et al (2010a), based on observations with SPIRE and PACS that are particularly sensitive to the warm inner envelope, reports a SiS abundance of 4 × 10 −6 , in good agreement with our finding for the inner layers.…”
Section: Molecular Abundancesmentioning
confidence: 99%